Level of involvement of clinical nurses in the evaluation of competence of nursing students - María Loreto Maciá-Soler; Víctor Manuel González Chordá; Pablo Salas Medina; Desirée Mena Tudela; Águeda Cervera Gasch; María Isabel Orts Cortés (Universidad de Antioquia, 2014)
Objective. To determine the level of involvement of clinical nurses accredited by the Universitat Jaume I (Spain) as mentors of practice (Reference Nurses) in the evaluation of competence of nursing students. Methodolgy. Cross-sectional study, in which the "Clinical Practice Assessment Manual'' (CPAM) reported by reference 41 nurses (n=55) were analyzed. Four quality criteria for completion were established: with information at least 80% of the required data, the presence of the signature and final grade in the right place. Verification of learning activities was also conducted. Data collection was performed concurrently reference for nurses and teachers of the subjects in the formative evaluations of clinical clerkship period in the matter "Nursing Care in Healthcare Processes ", from March to June 2013. Results. 63% of CPAM were completed correctly, without reaching the quality threshold established (80%). The absence of the signature is the main criteria of incorrect completion (21%). Nine learning activities do not meet the quality threshold set (80%) (p < 0.05). There are significant differences according to clinical units p < 0.05. From the 30 learning activities evaluated in the CPAM, it can be stated that nine of them do not reach the verification threshold established (80%), therefore it cannot be assumed that these activities had been completed by students and evaluated by the RefN throughout the clinical clerkship period. Conclusion. The level of involvement of Reference Nurse cannot be considered adequate, although strategies to encourage involvement through collaboration and training must be developed.